Ten-Year Experience Outcomes of a Day Treatment for Children and Adolescents with Psychiatric Disorders - (:unkn) unknown (AVES, 2019)
Introduction: It was aimed to evaluate the efficacy of a day treatment clinic in Turkey and which has been serving for ten years for children and adolescents with psychiatric disorders. Methods: 262 patients who completed day treatment within ten years were tested at intake and discharge. The patients' functioning was assessed using the Children's Global Assesment Scale (CGAS), Clinical Global Impression Scale (CGIS), state-trait anxiety inventory for children, depression rating scale for children, Coopersmith self-esteem inventory for children. Pre/post treatment comparisons were made on same variables. Results: Statistical analyses showed that, improvement was maintained on all measures. The high CGAS scores at discharge were showed well-being and good functioning of patient& The CGIS scores varied from moderately disturbed (4.83 +/- 0.88) to much improved (2.55 +/- 0.93) demonstrated that treatment responses showed improvement. Wilcoxon T tests showed that patients were significantly more anxious and depressive at intake and had more problems in self esteem. Statetrait anxiety inventory for children and depression rating scale for children scores decreased and Coopersmith self-esteem inventory for children scores improved with day treatment. Conclusion: This study points that as results of ten-year experience, day treatment approach seems effective and therefore to be the treatment of choice for treating children and adolescents with psychiatric disorders. It also shows the necessity of a treatment that combines multiple modalities like day treatment and day treatment must be more generalize for these patient population.
Keywords: Day treatment; children; adolescent; psychiatric disorders; RESIDENTIAL-TREATMENT; THERAPY; COST